Overexpression of the Synthetic Chimeric Native-T-phylloplanin-GFP Genes Optimized for Monocot and Dicot Plants Renders Enhanced Resistance to Blue Mold Disease in Tobacco (N. tabacum L.) - Dipak K. Sahoo; Sumita Raha; James T. Hall; Indu B. Maiti (The Scientific World Journal)
To enhance the natural plant resistance and to evaluate the antimicrobial properties of phylloplanin against blue mold, we have expressed a synthetic chimeric native-phylloplanin-GFP protein fusion in transgenic Nicotiana tabacum cv. KY14, a cultivar that is highly susceptible to infection by Peronospora tabacina. The coding sequence of the tobacco phylloplanin gene along with its native signal peptide was fused with GFP at the carboxy terminus. The synthetic chimeric gene (native-phylloplanin-GFP) was placed between the modified Mirabilis mosaic virus full-length transcript promoter with duplicated enhancer domains and the terminator sequence from the rbcSE9 gene. The chimeric gene, expressed in transgenic tobacco, was stably inherited in successive plant generations as shown by molecular characterization, GFP quantification, and confocal fluorescent microscopy. Transgenic plants were morphologically similar to wild-type plants and showed no deleterious effects due to transgene expression. Blue mold-sensitivity assays of tobacco lines were performed by applying P. tabacina sporangia to the upper leaf surface. Transgenic lines expressing the fused synthetic native-phyllopanin-GFP gene in the leaf apoplast showed resistance to infection. Our results demonstrate that in vivo expression of a synthetic fused native-phylloplanin-GFP gene in plants can potentially achieve natural protection against microbial plant pathogens, including P. tabacina in tobacco.